2019
DOI: 10.1186/s12915-019-0676-y
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the genetically tractable crustacean Parhyale hawaiensis reveals the organisation of a sensory system for low-resolution vision

Abstract: Background Arthropod eyes have diversified during evolution to serve multiple needs, such as finding mates, hunting prey and navigating in complex surroundings under varying light conditions. This diversity is reflected in the optical apparatus, photoreceptors and neural circuits that underpin vision. Yet our ability to genetically manipulate the visual system to investigate its function is largely limited to a single species, the fruit fly Drosophila melanogaster . Here… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 89 publications
(102 reference statements)
0
25
0
Order By: Relevance
“…Screening pigment granules contract inward to tightly encircle the rhabdom in bright light, then move away from the light path in darkness, functioning as a pupil. Though not widely reported in marine arthropods, it has been observed in the mantis shrimp G. oerstedii (King & Cronin, 1994a, 1994b, a horseshoe crab, Limulus polyphemus (Miller & Cawthon, 1974) and the amphipod Paryhale hawaiensis (Ramos et al, 2019), a diverse mix of arthropod taxa.…”
Section: Photoreceptor Screening Pigmentsmentioning
confidence: 99%
“…Screening pigment granules contract inward to tightly encircle the rhabdom in bright light, then move away from the light path in darkness, functioning as a pupil. Though not widely reported in marine arthropods, it has been observed in the mantis shrimp G. oerstedii (King & Cronin, 1994a, 1994b, a horseshoe crab, Limulus polyphemus (Miller & Cawthon, 1974) and the amphipod Paryhale hawaiensis (Ramos et al, 2019), a diverse mix of arthropod taxa.…”
Section: Photoreceptor Screening Pigmentsmentioning
confidence: 99%
“…However, our current knowledge of the genes involved in vision and 820! phototransduction, i.e., the conversion of light to electrochemical signals, is severely limited across decapod crustaceans (Henze and Oakley, 2015;Ramos et al, 2019;Zhang et al, 2019), ! Page -39with all crab data restricted to only a few eubrachyurans.…”
Section: Visual Pigments and Phototransductionmentioning
confidence: 99%
“…Our investigations on T. saltator indicate for the first time in Crustacea the existence of an area located in the DP of its eye specialised in detecting certain wavelength ranges involved in the perception of skylight cues. We still don’t know the role of R5 dominant in DP, however, in Parhyale hawaiensis , the spectral absorption bands estimated from the genetic results differed between R1-4 and R5 (Ramos et al, 2019). Therefore, R5 cell of T. saltator also might have different colour absorption band.…”
Section: Discussionmentioning
confidence: 97%
“…We assumed that the structural specializations of the retina determines the functional differences between DP and VP, therefore, we estimated roughly the visual filed from the light microscopic data. Since the number of the ommatidia of T. saltator increases with the growth of the body as reported for Parhyale hawaiensis (Ramos et al, 2019) and smaller ommatidial crystalline cones are frequently found at the peripheral region of the eye, we omitted these small ommatidia which possess small crystalline cones when we estimated the visual field. The visual field size in T. saltator were investigated using their pseudopupil (Beugnon et al, 1986); the individuals could potentially detect visual stimuli at 101 ° of vertical elevation.…”
Section: Discussionmentioning
confidence: 99%